Paradoxical glomerular filtration of carbon nanotubes - Ruggiero, Alessandro (National Academy of Sciences, 2010)
The molecular weight cutoff for glomerular filtration is thought to be 30–50 kDa. Here we report rapid and efficient filtration of molecules 10–20 times that mass and a model for the mechanism of this filtration. We conducted multimodal imaging studies in mice to investigate renal clearance of a single-walled carbon nanotube (SWCNT) construct covalently appended with ligands allowing simultaneous dynamic positron emission tomography, near-infrared fluorescence imaging, and microscopy. These SWCNTs have a length distribution ranging from 100 to 500 nm. The average length was determined to be 200–300 nm, which would yield a functionalized construct with a molecular weight of ∼350–500 kDa. The construct was rapidly (t(1/2) ∼ 6 min) renally cleared intact by glomerular filtration, with partial tubular reabsorption and transient translocation into the proximal tubular cell nuclei. Directional absorption was confirmed in vitro using polarized renal cells. Active secretion via transporters was not involved. Mathematical modeling of the rotational diffusivity showed the tendency of flow to orient SWCNTs of this size to allow clearance via the glomerular pores. Surprisingly, these results raise questions about the rules for renal filtration, given that these large molecules (with aspect ratios ranging from 100:1 to 500:1) were cleared similarly to small molecules. SWCNTs and other novel nanomaterials are being actively investigated for potential biomedical applications, and these observations—that high aspect ratio as well as large molecular size have an impact on glomerular filtration—will allow the design of novel nanoscale-based therapeutics with unusual pharmacologic characteristics.